Optimisation of diesel degradation and growth kinetic modelling by Antarctic Janthinobacterium lividum - Yap, How Swen; Khalid, Farah Eryssa; Wong, Rasidnie Razin; Convey, Peter; Sabri, Suriana; Abdul Khalil, Khalilah; Zulkharnain, Azham; Merican, Faradina; Shaari, Hasrizal; Ahmad, Siti Aqlima (Elsevier, 2025)
Fuel spills pose significant pollution threats to Antarctic terrestrial environments. Biological remediation offers a sustainable solution for restoring these polluted sites. Indigenous microorganisms capable of degrading diesel hydrocarbons at low temperatures could have the potential to restore polluted sites in Antarctic regions. This study represents the first comprehensive investigation into the effects of physiochemical conditions on diesel biodegradation and the growth kinetics of Janthinobacterium lividum, a native Antarctic bacterium previously identified for its diesel-degrading and biosurfactant-producing capabilities at low temperatures. Using a one-factor-at-a-time (OFAT) approach followed by response surface methodology (RSM), we optimised key culture conditions (10.00 °C, 0.00 % NaCl, 1.49 g/L NH4Cl, pH 7.05, 5.67 % v/v initial diesel concentration, and 14.10 % v/v inoculum size), achieving a five-fold enhancement in total petroleum hydrocarbon degradation, reaching 20.57 mg/mL. The Aiba-Edwards growth kinetics model mathematically best described the growth kinetics of the species in the presence of a toxic substrate. This study demonstrates statistically guided optimisation strategies for enhancing diesel biodegradation in Janthinobacterium species and demonstrates the bacteria's remarkable ability to tolerate high diesel concentrations even at low temperatures, reinforcing their potential for Antarctic bioremediation applications.